2002
DOI: 10.1002/pds.755
|View full text |Cite
|
Sign up to set email alerts
|

Prescription and non‐prescription analgesic use among the US adult population: results from the third National Health and Nutrition Examination Survey (NHANES III)

Abstract: Analgesic use among US adults is extremely high, specifically of non-prescription analgesics. Given this, health care providers and consumers should be aware of potential adverse effects and monitor use closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
126
3
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 40 publications
21
126
3
4
Order By: Relevance
“…Similar to our fi ndings in Turkey, many studies have also shown there is a signifi cant gender difference in the prevalence of analgesic use among adult population. 2,3,6,15,13,19 Studies conducted in the United States, Sweden, and Norway have shown an association between age and analgesic use. 6,7,12,16 Corroborating this fi nding, our study found higher prevalence of analgesic use in older ages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our fi ndings in Turkey, many studies have also shown there is a signifi cant gender difference in the prevalence of analgesic use among adult population. 2,3,6,15,13,19 Studies conducted in the United States, Sweden, and Norway have shown an association between age and analgesic use. 6,7,12,16 Corroborating this fi nding, our study found higher prevalence of analgesic use in older ages.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,12,16 Studies have shown that the majority of analgesics are non-prescription and over-the-counter (OTC) drugs, and that painkillers have a major share among OTC drugs. 13,15,16,18 In Turkey, studies also have indicated high rates of irrational use of prescribed and non-prescribed analgesics. 4,14,17 Not only can improper or irrational use of analgesics lead to increased morbidity and mortality rates and deterioration of quality of life, but also it can give rise to misusing RESUMO OBJETIVO: O uso de analgésicos tem sido amplamente reconhecido com um grande problema de saúde pública com importantes conseqüências na Turquia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 In the United States, the percentage of individuals who use analgesics reach 76%. 17 Diuretics also show variable percentages of use in the population, with values of 24.6% and 36.9% being recorded among men and women aged 75 years or more, respectively, in a study performed in the United States. 7 A study performed in Holland with hospitalized patients aged 75 years or more observed 37.7% of use of diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Os antiinflamatórios não-esteróides (AINE) integram o grupo dos fármacos mais comumente prescritos em todo o mundo e estão entre os mais utilizados nas práticas de automedicação [1][2][3][4] . Nos Estados Unidos, respondem por mais de 70 milhões de prescrições e mais de 30 bilhões de comprimidos de venda livre comercializados anualmente 5 .…”
Section: Introductionunclassified